Childhood vision impairment and blindness in West Africa: public health measures and implications for systemic health - Yeh, Caleb; Huang, Crystal; Huang, Ye; Hartley, Caleb D.; Fashina, Tolulope; Ashby, Nathaniel; Miller, Chase; Shantha, Jessica G.; Justin, Grant A.; Chan, R. V. Paul; Mattia, John G.; Vandy, Matthew J.; et al. (Frontiers in Medicine, 2024)
Childhood blindness is an issue of global health impact, affecting approximately 2 million children worldwide. Vision 2020 and the United Nations Sustainable Development Goals previously identified childhood blindness as a key issue in the 20th century, and while public health measures are underway, the precise etiologies and management require ongoing investigation and care, particularly within resource-limited settings such as sub-Saharan Africa. We systematically reviewed the literature on childhood blindness in West Africa to identify the anatomic classification and etiologies, particularly those causes of childhood blindness with systemic health implications. Treatable causes included cataract, refractive error, and corneal disease. Systemic etiologies identified included measles, rubella, vitamin A deficiency, and Ebola virus disease. While prior public health measures including vitamin A supplementation and vaccination programs have been deployed in most countries with reported data, multiple studies reported preventable or reversible etiologies of blindness and vision impairment. Ongoing research is necessary to standardize reporting for anatomies and/or etiologies of childhood blindness to determine the necessity of further development and implementation of public health measures that would ameliorate childhood blindness and vision impairment.